Novel Assessment Tool For Coronary Artery Disease Severity During Screening Mammography. Issue 10 (3rd October 2018) - Ružičić, Dušan; Dobrić, Milan; Vuković, Mira; Hrnčić, Dragan; Đorđević, Slavica; Ružičić, Milijana; Aleksandrić, Srđan; Đorđević-Dikić, Ana; Beleslin, Branko
ABSTRACT: Breast arterial calcifications (BACs) are common findings on mammography which are associated with an increased risk of the coronary artery disease (CAD). Our aim in the current study was to design measurement instruments of CAD prediction, with or without BACs, and its discriminatory validity in the diagnosis of CAD (expressed by Syntax score) in women. This was observational, prospective study in the women cohort which underwent mammography and angiography. In this study we have demonstrated that the total 'The Breast Arterial Calcification and Coronary Artery Disease Scale' (BACCADS) was good additional diagnostic tool for detection of patients with severe CAD.